Impact of health education on footwear practices in reducing low back pain among patients in Rivers State, Nigeria - Ubom, Ime M.; Echem, Richard C.; Madume, Anelechi Kenneth (PT. Mega Science Indonesia, 2024)
Joint dysfunction and increased pressure on the spinal discs can also occur, leading to disc degeneration or herniation and further stressing the lower back. The study aimed to investigate the impact of health education on footwear practices in reducing low back pain among patients in Rivers State, Nigeria. Low back pain is a common issue that affects many individuals and can be influenced by various factors, including footwear choices. The study included a sample of 50 participants from the University of Port Harcourt Teaching Hospital (UPTH) consisting of 45 individuals with nonspecific low back pain and 5 patients diagnosed with spinal stenosis. Participants were selected using stratified and non-proportional sampling techniques from a population of 170 individuals at UPTH. The Health Education Impact on Footwear Practices and Low Back Pain Questionnaire (HEIFPLBPQ) was used as the main instrument. Descriptive and inferential statistics were employed to analyze the collected data. The findings indicated that the health education intervention programme had a significant impact on both footwear practices and the reduction of low back pain among the patients. Participants gained knowledge about important factors such as body mass index, comfort/style, foot morphology, and affordability. Comfort/style was a priority for 40% of the participants, while 90% emphasized affordability in their footwear choices. The health education programme led to improvements in pain experiences, including decreased pain intensity and discomfort, as well as a reduction in pain exacerbation during ambulation. It was concluded that the health education programme resulted in notable improvements in pain experiences, including decreased pain intensity and discomfort, as well as a reduction in pain exacerbation during ambulation. It was recommended that to effectively address the needs of patients with low back pain, healthcare professionals and policymakers should customize health education interventions on footwear practices.